Animal Mitochondrial DNA Replication - Ciesielski, G. L.; Oliveira, M. T. [UNESP]; Kaguni, L. S. (Elsevier, 2016)
Recent advances in the field of mitochondrial DNA (mtDNA) replication highlight the diversity of both the mechanisms utilized and the structural and functional organization of the proteins at mtDNA replication fork, despite the relative simplicity of the animal mtDNA genome. DNA polymerase γ, mtDNA helicase and mitochondrial single-stranded DNA-binding protein-the key replisome proteins, have evolved distinct structural features and biochemical properties. These appear to be correlated with mtDNA genomic features in different metazoan taxa and with their modes of DNA replication, although substantial integrative research is warranted to establish firmly these links. To date, several modes of mtDNA replication have been described for animals: rolling circle, theta, strand-displacement, and RITOLS/bootlace. Resolution of a continuing controversy relevant to mtDNA replication in mammals/vertebrates will have a direct impact on the mechanistic interpretation of mtDNA-related human diseases. Here we review these subjects, integrating earlier and recent data to provide a perspective on the major challenges for future research. © 2016 Elsevier Inc.
Keywords: Animal phylogeny; DNA helicase; DNA polymerase; Mitochondria; Mitochondrial DNA; Replication; Replisome; Single-stranded DNA-binding protein